PENGEMBANGAN MEDIA PEMBELAJARAN DENGAN KUIS EDUKASI COC BERBASIS APLIKASI LECTORA INSPIRE PADA PEMBELAJARAN AKUNTANSI UNTUK MENINGKATKAN MINAT BELAJAR SISWA DI SMK NEGERI 1 KARANGANYAR - Rahmawati, Diah; Witurachmi, Sri; -, Sohidin (FKIP Universitas Sebelas Maret, 2016)
ABSTRACTThe objectives of this research are: (1) to investigateÂ the feasibility of the learning media with Lectora Inspire application-based Coins of Accounting Competition (COC) educational quiz; and (2) to investigate the effectiveness ofÂ the learning media developed with Lectora Inspire application-based Coins of Accounting Competition (COC) educational quiz in Accounting to improve the learning interest of the students of State Vocational High School 1 of Karanganyar. This research used the research and development (R&D) method. Its samples were the students in Grade X Accounting 1 and Grade X Accounting 2 as experimental class and control class respectively. They were determined by using the random sampling technique. The procedure for the development of the learning media referred to the one claimed by Borg and Gall with some modification. The data of research were collected through questionnaire and documentation. The data of the learning interest level were validated by using the construct validity. They were analyzed by using the statistical descriptive analysis and the statistical inferential analysis. The result of research shows that the learning media developed with Lectora Inspire application-based Coins of Accounting Competition (COC) educational quiz in Accounting learning is feasible to be used based on the validation of a learning media expert (93.61%), a learning material expert (80.89%), a practitioner (79%); and the students. the developed material belonged to âgoodâ and very goodâ categories. In addition, the developed learning media is effective to improve the learning interest of the students as indicated by the p-value = 0.000 < 0.05. The use of the Lectora Inspire application-based learning media is very much required to improve the learning interest of the students. Thus, the development of the learning media with Lectora Inspire application-based Coins of Accounting Competition (COC) educational quiz in Accounting learning can improve the learning interest of the students in Grade X Accounting 1 of State Vocational High School 1 of Karanganyar.Keywords: Learning media, educational quiz, Lectora Inspire, learning interestÂ Â ABSTRAKPenelitian ini bertujuan untuk: (1) Mengetahui kelayakan media pembelajaran dengan kuis edukasi COC berbasis aplikasi Lectora Inspire, dan (2) Mengetahui keefektifan media pembelajaran dengan kuis edukasi COC berbasis aplikasi Lectora Inspire pada pembelajaran akuntansi untuk meningkatkan minat belajar siswa di SMK Negeri 1 Karanganyar. Metode penelitian yang digunakan adalah penelitian dan pengembangan (R&D). Subjek penelitian adalah siswa kelas X Akuntansi 1 dan X Akuntansi 2 sebagai kelas eksperimen dan kelas kontrol yang diambil dengan teknik random sampling. Prosedur pengembangan media pembelajaran dengan kuis edukasi COC berbasis aplikasi Lectora Inspire dilakukan berdasarkan langkah-langkah pengembangan menurut Borg and Gall dengan modifikasi. PengumpulanÂ data dilakukan dengan instrumen berupa angket dan dokumentasi. Validitas instrumen menggunakan validitas konstruk pada angket minat belajar. Analisis data menggunakan analisis statistik deskriptif dan analisis statistik inferensial. Hasil penelitian menunjukkan bahwa produk media pembelajaran dengan kuis edukasi COC berbasis aplikasi Lectora Inspire layak digunakan berdasarkan validasi ahli media (93,61%), ahli materi (80,89%), praktisi (79%), serta penilaian siswa (87,70%) yang termasuk kategori âbaikâ dan âsangat baikâ. Media pembelajaran dengan kuis edukasi COC berbasis aplikasi Lectora Inspire memiliki keefektifan untuk meningkatkan minat belajar siswa (p = 0,000 < 0,05). Penggunaan media pembelajaran berbasis aplikasi Lectora Inspire sangat dibutuhkan guna meningkatkan minat belajar siswa. Simpulan penelitian ini adalah pengembangan media pembelajaran denga kuis edukasi COC (Coins of Accounting Competition) berbasis aplikasi Lectora Inspire pada pembelajaran akuntansi dapat meningkatkan minat siswa kelas X Akuntansi 1 SMK Negeri 1 Karanganyar.Kata Kunci : media pembelajaran, kuis edukasi, lectora inspire, minat belajar